Theoretical comparison of 0.78% tensile strained InGaAs/InAlGaAs and InGaAs/InGaAsP quantum-well lasers emitting at 1.55 μm - Khoo, Hong Khai (2014)
Proceedings of SPIE - The International Society for Optical Engineering